Ultrastructural changes of ganglionic and M?ller’s cells of the rat’s retina caused by methanol intoxication (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Methyl alcohol (methanol) is a strong toxic substance, which is used in varnish-and-paint industry, at the petrol stations, etc that increases the possibility of its incidental or chronic influence on the human organism. According to the clinical and experimental data methanol primarily damage the optic nerve, retina and the brain tissues. Therefore, it is important to study mechanisms of the damaging effect of methanol on live tissues, namely, the retina of the experimental animal deeper at the subcellular level. Objective. Electronic-microscopic study of changes of the ganglionic cells (GC) and processes of M?ller’s cells (PMC) that surround GC of the retina of white rats in dynamics (1–14 days) after single intraabdominal introduction of methanol in the dose of 2.5 g/kg of the body mass.  Material and methods. The work was done on 18 white Wistar’s rats of 250–300 g of weight, which were subdivided into two groups: 1- a group under study where the rats were given single injection of methanol in the dose of 2.5 f/kg of the body mass. II — a group with control animals, which were introduced a physiological solution in the same volume. There was investigated the ultrastructure of GC and PMC of the rats’ retina in 1, 3, 7 and 14 days after introduction of methanol in the electronic microscope PEM-100–01. Results. It is shown that methanol caused primary and considerable damage of GC of the retina. The cells of small and middle size were the most vulnerable of GC. During the follow-up investigation destructive changes increased both on GC and PMC. It was found that mitochondria were the most vulnerable structures to the damage resulting in significant energy dysfunction of the cells. Parallel to the destruction signs there were signs of increased protein-synthesized activity in GC, which was a manifestation of compensation-restoration processes in them.
Keywords: Retina; ganglionic cells; processes of M?ller’s cells; ultrastructure; methanol